The working of the eurosystem - monetary policy preparations and decision-making – selected issues - Philippe Moutot; Alexander Jung; Francesco Paolo Mongelli (European Central Bank (ECB), 2008)
The ECB's monetary policy has received considerable attention in recent years. This is less the case, however, for its regular monetary policy preparation and decision-making process. This paper reviews how the factors usually considered as critical for the success of a central banking system and the federal nature of the Eurosystem are intertwined with its overall design and the functioning of its committee architecture. In particular, it examines the procedures for preparing monetary policy decisions and the role of the decision-making bodies and the committees therein. We suggest that technical committees, involving all national central banks (NCBs), usefully contribute to the regular processing of a vast amount of economic, financial and monetary data, as well as to the consensus building at the level of the Governing Council. A federal organisational structure, including a two-tier committee structure with the Executive Board taking the lead in preparing the monetary policy decisions and the Governing Council in charge of the decisions with collective responsibility for them, as well as committee work at the various hierarchical levels, contributes to the efficiency of the ECB's monetary policy decision-making, and thereby facilitates the maintenance of price stability in the euro area. A fully-fledged committee structure has also contributed to the smooth integration of non-euro area Member States into the Eurosystem's monetary policy decision-making process.
Keywords: E42; E58; F33; F42; 330; European economic and monetary integration; monetary arrangements; central banks and their policies.; Eurozone; Geldpolitik; Zentralbank; Gruppenentscheidung; EU-Staaten